PENGEMBANGAN DANA CADANGAN QARDH PADA ASURANSI SYARIAH - Ali Muhayatsyah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
This study discusses the development pattern of qardh reserves as an instrument of social funds in Takaful insurance. The use of qardh reserves at the beginning to cover the deficiencies in tabarru 'funds in assuming risks arising from the large number of participant claims. The limited use of qardh funds is a dilemma for corporations, as they can be utilized by companies to improve performance, and can be expanded as a social fund instrument by companies. In this study the problem discussed is how the development and use of instruments qardh funds on Takaful insurance. The development of qardh funds in sharia insurance can be divided into two uses, first as a reserve fund that serves as a cover for risk on tabarru 'funds. Secondly, qardh funds are used as social funds (Qardh Hasan). Development is done to expand the source of funds into the qardh funds, either internal or external parties are willing to include funds into qardh fund Takaful insurance. The use of productive qardh funds can be used to increase the amount of qardh's reserves, in addition to channeling qardh funds with social objectives, to enable companies, investors, and communities to engage in helping others by entrusting insurance companies as mediators in funding channels. Keywords: Qardh Fund, Tabarru 'Fund, Islamic Insurance.